Artificial photosynthesis using ultrathin 2D materials. (2022) - Pradhan, Sova Nika; Pradhan, Abanti; Dash, Barada P.; Sahoo, Prasanta K.; Sahoo, Naresh K.; Naik, Brundabana
Abstract: Ultrathin 2D nano materials are gaining enormous attention after Geim and co-worker reported graphene from mechano-chemical exfoliation of ordered graphite. The extraordinary optoelectronic and physico-chemical properties of ultrathin 2D nanomaterials owing to its unistructural features offer diversified applications. Artificial photosynthesis is a mimic process of natural photosynthesis that include a photocatalyst to fix and convert CO2 to clean fuel. Ultrathin 2D nano materials furnishes high active sites with maximum edge and interface area that determine the CO2 photo-conversion efficiency and selectivity. Here in, we have reported the summaries of synthesis, co-catalytic behavior, CO2 conversion efficiency and selectivity of ultrathin 2D nanomaterials for energy generation and fine chemical transformation. Graphene and its analogous i.e. Transition Metal Di-chalcogenides (TMDS), graphitic Carbon Nitrides (g-C3 N4), Metal Organic frameworks (MOF), Covalent Organic Frameworks (COF), MXenes, Layered Double Hydroxides ( LDH), Black Phosphorus (BP) and metal oxides like RuO2 /TiO2, etc. are categorized for photo-conversion of CO2 . Nanostructured geometry and higher active surface area of nanocatalysts are focused for the selective CO2 conversion.